Influence of Tool Wear on Surface State after Turning Stainless Steels - Neslušan, Miroslav; Čilliková, Mária; Mičietová, Anna; Čapek, Jiří (Manufacturing Technology Journal, 2018)
This paper deals with influence of tool wear on surface integrity after turning of stainless steels. Surface integrity is expressed in terms of structure transformation initiated by turning process as well as Barkhausen noise emission. Furthermore, components of cutting forces are also measured as a function of tool wear and their evolution along with developed flank wear VB is presented. The results indicate that presence of carbides in the matrix - their size and density play a significant role in the resistance of the matrix against the structure transformations. The results also indicate that Barkhausen noise technique is sensitive to structure transformations of austenite steels initiated by turning process.
Keywords: Turning; Structure; Stainless Steel; Barkhausen Noise